Reappraisal of fibrosis-4 index and non-alcoholic fatty liver disease fibrosis score for advanced fibrosis in average-risk population - Park, Huiyul; Yoon, Eileen L.; Kim, Mimi; Lee, Jonghyun; Cho, Seon; Jun, Dae Won; Nah, Eun-Hee (Frontiers in Medicine, 2022)
Background & Aim: The current cut-offs for fibrosis-4 (FIB-4) and non-alcoholic fatty liver disease fibrosis score (NFS) are suboptimal for screening because of low accuracy and high false-negative rates in average-risk populations. This study aimed to reappraisal the performance of FIB-4 and NFS in such average-risk populations. Methods: This is a cross-sectional study, which retrospectively reviewed the magnetic resonance elastography (MRE) data of 8,522 subjects. Individuals with history of significant alcohol consumption and those with positive viral serologic markers were excluded. Finally, 6,215 average-risk individuals were analyzed. Results: The area under the receiver operating characteristic curves (AUROCs) of FIB-4 for the diagnosis of advanced hepatic fibrosis was higher than that in the NFS especially in the metabolically healthy. The AUROCs of FIB-4 for in the average-risk population was also higher than that in the NFS (0.840 in FIB-4 vs. 0.798, P = 0.036). However, the sensitivity of FIB-4 and NFS was low (69.6% and 61.4%, respectively) in applying the current cut-off of FIB-4 (1.3 (2.0)) and NFS (-1.455 (0.12)). At cut-off of FIB-4 at 1.0, sensitivity (90.2%) and negative predictive value (99.7%) were improved. Conclusions: The diagnostic performance of FIB-4 was better than that of NFS for screening hepatic fibrosis in average-risk populations. It is recommended to use FIB-4 rather than NFS, when screening for hepatic fibrosis in general population.